hambatan Analisis Faktor Hambatan Penerapan E-Government Kelurahan Kedungwuluh Menggunakan Framework Technology-Organization-Environment (Toe) (Studi Kasus: Website Kelurahan Kedungwuluh): (Studi Kasus: Website Kelurahan Kedungwuluh) - Nurmalasari, Eza; Susanto, Irwan; Kristiyanto, Daniel Yeri (LPPM UNIKA Santo Thomas Medan, 2022)
Kedungwuluh Village is a Government service unit at the smallest level. This study analyzes the barriers to implementing e-Government, focusing on the use of the Kedungwuluh village website. This study uses a Technology-Organization-Environment (TOE) approach. While the ease of technology for the community and public knowledge about the village website have a low score so that it becomes an obstacle in implementing the implementation of the Kedungwuluh Village website. The results of this study indicate that technology readiness, technological convenience for the government, technology benefits, leadership commitment, human resource readiness have good scores While the ease of technology for the community and public knowledge about the village website have a low score so that it becomes an obstacle in implementing the implementation of the Kedungwuluh Village website. Recommendations to help the Kedungwuluh Village Government are by conducting periodic socialization and educate to the community so that people understand the use of the Kedungwuluh Village website.